About the selectivity and reactivity of active nickel electrodes in C–C coupling reactions. Issue 24 (8th April 2020) - Beil, Sebastian B.; Breiner, Manuel; Schulz, Lara; Schüll, Aaron; Müller, Timo; Schollmeyer, Dieter; Bomm, Alexander; Holtkamp, Michael; Karst, Uwe; Schade, Wolfgang; Waldvogel, Siegfried R.
Abstract : Active anodes which are operating in highly stable protic media such as 1, 1, 1, 3, 3, 3-hexafluoroisopropanol are rare. Abstract : Active anodes which are operating in highly stable protic media such as 1, 1, 1, 3, 3, 3-hexafluoroisopropanol are rare. Nickel forms, within this unique solvent, a non-sacrificial active anode at constant current conditions, which is superior to the reported powerful molybdenum system. The reactivity for dehydrogenative coupling reactions of this novel active anode increases when the electrolyte is not stirred during electrolysis. Besides the aryl–aryl coupling, a dehydrogenative arylation reaction of benzylic nitriles was found while stirring the mixture providing quick access to synthetically useful building blocks.